Strategic Analysis of Establishing an Aircraft Engine MRO: A Feasibility Study in the Indonesian Aviation Market - Adzkia Salsabilla Widodo; Harimukti Wandebori (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
As a rapidly growing sector, the aviation market is highly open to development. Maintenance, particularly for major components like engines, is crucial and must comply with regulations. Establishing an Engine MRO facility shows a promising opportunity in the aviation sector. With over 640 commercial aircraft operating daily in Indonesia, the demand for engine maintenance and overhaul is increasing. However, limited local MRO capacity and capability force airlines or aircraft owners to outsource maintenance to foreign facilities, leading to higher costs, time, and logistical complexity. This study employs the I/O Model to analyze the feasibility of establishing a new local Engine MRO facility in Indonesia. The research utilizes industry, general environment, and competitor analyses, supported by market segmentation, to identify opportunities opening new engine MRO in Indonesia, resulting in a niche, growing market for the LEAP engine series capabilities. However, the study is highlighting the high initial investment required. Internal capabilities include skilled personnel, specialized tools, facilities, and strategic partnerships with suppliers or authorities. The implementation plan outlines five phases, from preliminary setup to long-term sustained growth. The study concludes that establishing a new Engine MRO in Indonesia can address demand gaps, reduce reliance on foreign facilities, and strengthen Indonesia's aviation industry. Recommendations focus on non-financial investments, including human resource development, lean operations, and adopting advanced technology.